Minimizing Total Implementation Cost of a 2-D Indoor Localization System with a Constant Accuracy for Underground Mine Tunnels - Vasquez-Perez, O; Espinoza-Perez, A (Springer Science and Business Media Deutschland GmbH, 2021)
In this paper, we introduce the problem of minimizing total implementation cost of a 2-D indoor localization system for underground mine tunnels, guaranteeing a constant accuracy. To address this problem, we propose a system based on Cell-ID technique and visible light communication (VLC) technology with square panels of light-emitting diode (LED) lights, which fixes the maximum position error in each cell by considering the distribution of overlapping and non-overlapping cells. Formally, our system is mainly defined by an easy-to-implement algorithm based on a simple order rule. In order to illustrate the usefulness of the proposal, an example is provided. Finally, potential applications in the industrial environments are discussed and future research is proposed. © 2021, Springer Nature Switzerland AG.
Keywords: Accuracy; Cost minimization; Indoor localization system; Visible light communication